Left lower lobe sleeve resection for endobronchial schwannoma - Liao, Hu; Song, Wenpeng; Chen, Nan; Chen, Fengning; Liu, Chengwu; Lin, Feng (Annals of Translational Medicine, 2018)
Schwannomas are mesenchymal neoplasms originating from Schwann cells of the nerve sheath. The tumor may appear anywhere in the body, while it has a predilection for extremities, trunk, retroperitoneum, head, and neck. Primary pulmonary schwannoma is extremely rare, accounting for less than 0.2% of all lung tumors. A 42-year-old man was incidentally discovered to have an endobronchial tumor, and we performed the left lower lobe sleeve resection to remove the mass completely. Postoperative histopathological findings confirmed a benign schwannoma. Although endobronchial schwannoma is extremely rare, follow-ups are crucial for monitoring tumor growth and reducing the risk of recurrence.